Stacking transgenic event DAS‐Ø15Ø7‐1 alters maize composition less than traditional breeding. Issue 10 (11th April 2017) - Herman, Rod A.; Fast, Brandon J.; Scherer, Peter N.; Brune, Alyssa M.; de Cerqueira, Denise T.; Schafer, Barry W.; Ekmay, Ricardo D.; Harrigan, George G.; Bradfisch, Greg A.
Summary: The impact of crossing ('stacking') genetically modified (GM) events on maize‐grain biochemical composition was compared with the impact of generating nonGM hybrids. The compositional similarity of seven GM stacks containing event DAS‐Ø15Ø7‐1, and their matched nonGM near‐isogenic hybrids (iso‐hybrids) was compared with the compositional similarity of concurrently grown nonGM hybrids and these same iso‐hybrids. Scatter plots were used to visualize comparisons among hybrids and a coefficient of identity (per cent of variation explained by line of identity) was calculated to quantify the relationships within analyte profiles. The composition of GM breeding stacks was more similar to the composition of iso‐hybrids than was the composition of nonGM hybrids. NonGM breeding more strongly influenced crop composition than did transgenesis or stacking of GM events. These findings call into question the value of uniquely requiring composition studies for GM crops, especially for breeding stacks composed of GM events previously found to be compositionally normal.